Ethical Aspects of the Guidelines for Medical Education for Students in their Clerkship Year at the Schulich School of Medicine and Dentistry During the COVID-19 Pandemic - Gignac, Christine; Markwell, Hazel (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2022)
Guidelines for clerkship training at one Canadian medical school – Western University’s Schulich School of Medicine and Dentistry – did not state the ethical principles associated with the decision to suspend and eventually resume clinical training during the COVID-19 pandemic. The absence of stated ethical principles was notable considering the impact these decisions had on various stakeholders, and since ethics plays a large role in the practice of medicine. This study assessed these guidelines using an ethical lens approach to identify ethical principles and tensions implicit in the guidelines. Clerkship is defined as the third year of training at this medical school, which consists of clinical rotations. While ethical principles were not documented, it was hypothesized that these could be identified within the guidelines. A literature search was conducted, which yielded a gap in knowledge concerning ethical considerations of clerkship clinical training. The guidelines were analyzed and ethical principles and tensions between conflicting principles were identified. The most prevalent principles were beneficence and non-maleficence. It is recommended that in the future, the ethical principles associated with guidelines responding to significant issues affecting undergraduate medical education be stated, in order to increase transparency to all parties involved, enhance communication with students, and to serve as an example of how ethics is applied in a medical education setting. One limitation of this study was the use of internal guideline documents, which were circulated internally but are not published.